Mechanical Characteristics of an Explosive in the Temperature Range 20–100°C - Beketov, A. P.; Efanov, A. N.; Nikul’shin, M. V.; Putilin, O. S. (Journal of applied mechanics and technical physics, 2025)
This paper presents the results of mechanical tests of specimens of the explosive under study. Stress–strain curves and Poisson’s ratio versus strain curves at a temperature of 20, 60, 80, 100°C are plotted. Temperature dependences of the mechanical characteristics of the explosive are obtained. The rigidity, strength, and deformability of the explosive are shown to decrease with increasing temperature.